Combining paper maps and smartphones in the exploration of cultural heritage - Pires, Antero Augusto Magalhães (2017)
Latest advances in technology allowed us to have, nowadays, powerful computing devices in our pockets. These advances have also allowed the rapid growth of Augmented Reality, which continues to expand into new areas where the integration of virtual and real worlds brings new and beneficial experiences. It is on these Augmented Reality capable devices that there may be a key that will open a door to a new experience in exploring cultural and historical sites, currently very dependent on paper and static information maps or mobile interactive applications that, although capable of providing real-time information, may not give users a contextualized view of the different cultural elements in their surrounding environment. The goal of this dissertation is to explore new ways to interact and view content associated with a cultural and historical site through a smartphone-focused application with Augmented Reality and location-aware features. Combining a paper map with a smartphone, the user can see virtual representations of sites, manipulate them in 3D, overlap historical cartography on the map or view relevant multimedia information, among others. In an effort to raise awareness of less known sites or whose location isn’t immediately apparent, the application alerts the user about sites near his position. Then, the application underwent various tests by potential users, in order to evaluate its concept and usability. In the end, it is expected to develop a new user interactive experience, as an attempt to increase interest and awareness of cultural and historic sites and their roles, and formulate recommendations on the development of heritage-oriented applications.